Demographic Factors Of Contraception (Implants And Iud) Among Women In Lelateng - Putu Sukma Megaputri; Ni Luh Ketut Bodi Adnyani (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2023)
Long-term contraceptive methods are contraception used by mothers to space out pregnancies to help mothers maintain health and have greater risks. The purpose of this study was to identify the acceptors' characteristics of IUD and implant users in the Lelateng Village. This research method is quantitative with a cross sectional approach. The sampling technique in this study was purposive sampling with a total sample of 63 respondents. The results of the study reported that the characteristics of respondents who used IUDs and implants were of reproductive age, namely 35 years, with the last education of high school, a multigravida and IUD acceptors were more ASN and implant acceptors were more IRT. The conclusion is that IUDs and implants are long-term contraceptive methods that can help mothers in the process of spacing pregnancies and avoid unwanted risks.